Local Technical Agroclimatic Committees (MTA): A detailed guide on its implementation step by step - Second Edition - Giraldo-Mendez, Diana; Navarro Racines, Carlos Eduardo; Martínez Barón, Deissy; Loboguerrero Rodriguez, Ana María; Gumucio, Tatiana; Martínez, Jesús David; Guzmán Lopez, Helmer; Ramírez Villegas, Julián Armando (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This manual provides step-by-step instructions for working on the MTA approach. It is aimed mainly at leading agricultural sector institutions interested in implementing a space for discussion in their region. This approach consists of eight steps, which are carried out with the participating institutions. Given the site-specific nature, some preparatory activities need to be done before each meeting. Throughout the manual, blue boxes will be highlighted to indicate gender and social inclusion considerations, and orange boxes to indicate relevant aspects for the proper development of the MTA. In this second edition, the manual has mitigation considerations (practices) and the monitoring and evaluation tools applied.